The features of cenopopulations structures of rare, endemic plant species Oxytropis almaatensis Bajt. from Trans-Ili Alatau mountains (Experimental biology, 2016)
Genus Oxytropis DC. is represented in Kazakhstan by 119 species of 15 sections, 36 species (32.5%) are endemic, and 10 included in the Red Book of Kazakhstan. One of the rare, narrowly endemic species of Kazakhstan is Oxytropis almaatensis, described by M.S.Baytenov according to E.Gorbunova and V.P.Goloskokov data from Syugaty and Toraigyr mountains in 1937 (eastern part of the Trans-Ili Alatau). Located in close vicinity of the largest megapolis of the republic as a city of Almaty and many other populated areas, ecosystems of Trans-Ili Alatau are experiencing huge recreational load, negative affecting on the vegetation cover. The age spectrum is important for evaluate the coenopopulations state and helps to conduct a modern diagnostic status and evaluate the future development. In 2015-2016 the authors have been found and studied characteristics of the demographic structure of the O.almaatensis 6 coenopopulations on territory of IA SNP. Most of them have a developmental spectrum with one maximum and only two coenopopulations (fifth and sixth) are bimodal spectrum with peaks in young vegetative and generative plants. The highest density of O.almaatensis noted in the sixth coenopopulations, the lowest - fourth coenopopulations.
Keywords: Oxytropis almaatensis; ontogenesis; age spectrum; cenopopulation; population.